2017
DOI: 10.1111/cpr.12346
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock transcription factor 1 promotes the proliferation, migration and invasion of osteosarcoma cells

Abstract: These data highlight an important role of HSF1 in proliferation, migration and invasion of osteosarcoma cells. Moreover, the expression of HSF1 was associated with prognosis in osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Other peculiarities in cancer cell behavior were also found to be suppressed by CL-43, more specifically, migration of HCT-116 cells (Figure 3A–3C ) and colony formation capacity (Figure 3D, 3E ). These effects clearly resemble the consequences of HSF1 knock-down, as shown recently [ 23 , 24 ]. We conclude that CL-43 by itself can reduce the growth of cancer cells and accordingly, their tumorigenicity.…”
Section: Discussionsupporting
confidence: 79%
“…Other peculiarities in cancer cell behavior were also found to be suppressed by CL-43, more specifically, migration of HCT-116 cells (Figure 3A–3C ) and colony formation capacity (Figure 3D, 3E ). These effects clearly resemble the consequences of HSF1 knock-down, as shown recently [ 23 , 24 ]. We conclude that CL-43 by itself can reduce the growth of cancer cells and accordingly, their tumorigenicity.…”
Section: Discussionsupporting
confidence: 79%
“…All the 10 studies investigated the prognostic role of HSF1 in OS, and only three studies focused on disease-free survival (DFS). 9 , 15 , 16 HR with the corresponding 95% CI was directly extracted through multivariate analyses in seven studies, 8 14 and HR in the remaining three studies 15 17 was calculated from Kaplan–Meier survival curves by the Tierney’s methods. The quality of all the 10 studies was assessed by NOS, and the scores ranged from 5 to 8 (median 6.7), suggesting that the methodological quality was relatively high ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Identification of many prognostic factors in recent years has helped more accurate prognostic prediction of tumor patients. Growing studies have demonstrated that HSF1 is overexpressed in a series of solid tumors such as esophageal squamous cell carcinoma (ESCC), 8 , 9 breast cancer (BC), 10 , 11 hepatocellular carcinoma (HCC), 12 14 osteosarcoma, 15 non-small-cell lung cancer (NSCLC), 16 and pancreatic cancer. 17 Furthermore, evidence implies that the elevation of HSF1 expression is correlated with poor survival of tumor patients.…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, a high HSF1 level was associated with histological grade, larger tumour size, and nodal involvement [ 14 ]. High expression of HSF1 protein is significantly associated with aggressive disease and poor survival in CRC, ESCC, ccRCC and osteosarcoma [ 12 , 13 , 16 18 ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%